Political Practices of the Popular Sectors in Río de Janeiro: Urbanization of the Favela Santa Marta - Maximiliano Duarte Acquistapace (Íconos)
This article analyzes the political practices of the residents of the favelas of Río de Janeiro through ethnographic fieldwork conducted between 2010 and 2015 in the favela of Santa Marta. Politics is understood here in its broader sense as the way in which disagreements are managed and consensus is reached amongst the local population. To understand these practices means to uncover and illuminate the mechanisms that allow for the construction of the sense of what is legitimate and what is possible, as well as the channels and mechanisms for resolving local disputes. Specifically, this study examines how residents organize themselves to make demands on the State and how they interface with the State in a contemporary context marked by projects of urban renewal and the regularization of the favelas.